Impact of audit committee characteristics on the earnings quality - Nik Mohd Norfadzilah, Nik Mohd Rashid; Suleman Ali, Eyal Awwad (2019)
The objective of this paper is to explore the characteristics of the Audit Committee (AC) (namely: audit committee independence, and number of meetings) in the public companies listed on the Amman Stock Exchange (ASE), and then look at their impact on the quality of earnings expressed in the continuity of earnings in the future. So, in the past years, the role of the Audit Committees as an institutional governance mechanism has increased, which aims to protect the interests of the shareholders and preserve the rights of companies, after the failures financial and administrative of many foreign and local companies.